Effect of tilting angles on the performance of reflective and transmitting types of fiber optic-based displacement sensors - Yasin, M.; Harun, Sulaiman Wadi; Kusminarto, -; Karyono, -; Lelono, D.; Samian, -; Zaidan, A.H.; Ahmad, Harith (IOP Publishing, 2010)
The performances of the fiber optic-based displacement sensor with reflective and transmitting techniques were investigated. The effects of axial displacement on the detected voltage were investigated for different tilting angles of the reflective and receiving fibers. Three types of light sources were used, yellow and red He-Ne including a green pointer laser at peak wavelengths of 594, 633, and 533 nm correspondingly. The highest sensitivity and resolution were obtained at 0.0017 mV/mu m and 4 mu m, respectively with the employment of a 594 nm laser as the light source. These were attributed to the output power and beam quality of the laser which was the highest. The tilting angles didn't change the sensitivity and resolution of the sensors in both setups. The widest linear range was obtained at 2410 mu m with the transmitting technique. The simplicity of the design, high degree of sensitivity, linear range, non-contact measurement and low cost fabrication make it suitable for industrially-orientated applications that include control and micro-displacement in the hazardous region.